NTT DALAM CAHAYA ACTOR NETWORK THEORY: Studi Kasus Human Trafficking Berkedok Pengiriman Tenaga Kerja Indonesia di Nusa Tenggara Timur - Suwarno, Windy Paskawati; Wiloso, Pamerdi Giri; Therik, Wilson M.A. (KRITIS, 2018)
The case of human trafficking in NTT has become an unresolved case. Most of the case of human trafficking in NTT are migrant workers. Human trafficking cases are effected by the actors involved in the network of problems. ANT (Actor Network Theory) is used as a review to describe the various roles of actors in human trafficking networks and is used to find the point of problem of human trafficking cases in NTT. The results of this study indicate an indication of the onvolvement of actors of human trafficking groups participating in trafficking networks. And poverty is a major factor in the rise and fall of human trafficking in NTT. And the poverty is a major factor in the unstoppable of human trafficking in NTT. The results of this study also led to the solution of economic empowerment as a way out of poverty to end human trafficking cases in NTT.